Promoter Methylation of QKI as a Potential Specific Biomarker for Early Detection of Colorectal Cancer - Zhang, Lei; Li, Dapeng; Gao, Lijing; Fu, Jinming; Sun, Simin; Huang, Hao; Zhang, Ding; Jia, Chenyang; Zheng, Ting; Cui, Binbin; Liu, Yanlong; Zhao, Yashuang (Frontiers in Genetics, 2022)
Early and specific detection of cancer provides an opportunity for appropriate treatment. Although studies have suggested that QKI is a tumor suppressor gene, no studies have evaluated the diagnostic effect of QKI methylation in CRC (colorectal cancer). Here, we evaluated the methylation status of QKI genes by integrating the methylation data of tissues and cell lines of multiple cancer types. The diagnostic performance of QKI was analyzed in the discovery dataset from TCGA CRC 450K array (n = 440) and tested in the test sets (n = 845) from the GEO. The methylation level of QKI was further validated in our independent dataset (n = 388) using tar-geted bisulfite sequencing. All detected CpG sites in the QKI promoter showed CRC-specific hypermethylation in 31 types of tumor tissue. In the discovery dataset, six consecutive CpG sites achieved high diagnostic performances, with AUCs ranging from 0.821 to 0.930. In the test set, the region (chr6: 163,834,452-163,834,924) including four consecutive CpG sites had robust diagnostic ability in distinguishing CRC and adenoma from normal samples. In the validation da-taset, similar robust results were observed in both early and advanced-stage CRC patients. Also, QKI exhibited hypermethylation in the cfDNA of patients with CRC (n = 14). Collectively, the QKI promoter is a CRC-specific methylation biomarker, and holds great promise for improving the diagnosis using minimally invasive biopsy.